The impact of mindfulness on university students’ academic achievement: A systematic literature review with VOSviewer - Galdo Jiménez, Alfredo José (2021)
The current research study objectives are focused on determine in first place the level impact of the exclusion of some key terms on the co-occurrence variable about the research topic “The impact of mindfulness on university students’ academic achievement: A systematic literature review with VOSviewer”; in second place, determine countries with the highest citation per document rate and finally define the impact level of the reduction of the amount of documents and the increase of the amount of citations on the determination of the authors with the highest citation- per document- rate. Study design: Sistematic review with cross-sectional.analysis and descriptive method. It is used an intentional and non-probabilistic sampling technique. The sample is conformed by 51 documents chosen from Scopus database for the period 2015-2020 and related to the research study equation. For the analysis it is used VOSviewer software. The results obtained shew that due to the fact the words: mindfulness and academic achievement have the highest impact, it would be advisable to deepen on publications related to psychology. In adittion, it must be a priority to consider United States of America, Germany and Australia publications because of their higher citation-per-document rate. Finally, it is concluded that the reduction of the amount of documents by one and the increase of the amount of citations by four have an impact on the determination of the authors with the highest citation-per-document rate. Hahne A., Mccaleer R. and Mcconville are the recommended authors because of their highest citation-per-document rate and their relatively recent publications.